SCIENTIFIC - METHODOLOGICAL BASIS OF DETERMINING THE BRAND VALUE OF ENTERPRISES (Marketing Journal, 2025)
The article examines the issue of brand valuation in enterprises from a scientific and methodological perspective. Based on a study of 30 firms in the Namangan region, surveys and multiple regression analysis were applied, identifying brand loyalty, brand awareness, advertising expenditure, and product quality as key determinants. The results showed that loyalty and awareness are the most important factors in determining brand value. The proposed methodology provides practical guidance for companies to impr ove marketing strategies, plan innovations, and justify market entry decisions.
Keywords: Brand value; brand loyalty; brand awareness; advertising expenditure; product quality; regression analysis; marketing strategy. 312